KEPRAKTISAN MODEL PEMBELAJARAN THINK PAIR SHARE DAN RESPON SISWA PADA PEMBELAJARAN BERBICARA DI SEKOLAH MENENGAH PERTAMA - Joko Purwanto, M. Pd.; Yuli Widiyono (p-ISSN 2356-0576, 2021)
Abstract: The development of the Think pair share model was developed to improve students' critical thinking skills in speaking learning in junior high schools. The development of the Think pair share model is carried out by adapting the ten stages of the Research and Development model from Borg and Gall. From the results of the model development stages, it is known that the Think Pair Share practical model in learning to speak has an average score of 2.88 or good category. The results of students' responses to the Think Pair Share model in speaking learning obtained an average result of 77.98 or good categories. Through the process of sharing information on ideas that students have, it is hoped that through a model of sharing thoughts, speaking skills will be more focused and produce quality thinking or critical thinking, by paying attention to the principle of benefits and the ability to explore in order to solve problems properly. Keywords: model, think pair share, student response, speaking